PEMIKIRAN SUTAN TAKDIR ALISYAHBANA TENTANG NILAI, MANUSIA, DAN KEBUDAYAAN - Hadi, Sumasno (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2011)
Sutan Takdir Alisyahbana is one of the Indonesian greatest intellectuals concerned with human and cultural issues.He is a man of letters, linguist, philosopher and social scientist.His background of knowledge is different from most sociologists, anthropologists and historians so that it is not surprise that his thought of culture has its own style.His thoughts are rooted in humanism which developed inEurope since Renaissance to the rise of neo-positivism. According to him, a reality is a result of intellect and a movement of values.He believes that ethics generally is the core of individual, social, and cultural life. Ethical relationships of value are the main core of cultural issue. Human, as a creator of culture, has a dual nature. One side, human is a natural creature and on the other side, human is an intellectual/ reason creature. As a natural creature, human is subjected to natural laws which control his/her birth and physical life. Meanwhile, as an intellectual/ reason creature, according to him, human obedience to the law of reason defines humanity and allows human creates a high culture.Keywords: Sutan Takdir Alisyahbana, value, human, culture.